2009
DOI: 10.1158/0008-5472.can-08-4754
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor-γ Contributes to the Inhibitory Effects of Embelin on Colon Carcinogenesis

Abstract: Down-regulation of XIAP (X-linked inhibitor of apoptosis protein) sensitizes colon cancer cells to the anticancer effect of peroxisome proliferator-activated receptor-; (PPAR;) ligands in mice. The aims of this study were to evaluate the effect of embelin (2,5-dihydroxy-3-undecyl-1,4-benzoquinone), an antagonist of XIAP, on colon cancer, with a particular focus on whether PPAR; is required for embelin to exert its effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 36 publications
1
50
0
Order By: Relevance
“…The score of each variable was added to give a total microscopic damage score. Colonic neoplasms were diagnosed as previously described (12).…”
Section: Histopathologic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The score of each variable was added to give a total microscopic damage score. Colonic neoplasms were diagnosed as previously described (12).…”
Section: Histopathologic Analysismentioning
confidence: 99%
“…Western blot analysis and qPCR were performed as we described (12,20), and the following primary antibodies were used: anti-glyceraldehyde-3-phosphatedehydrogenase (GAPDH, Abcam), anti-p-STAT3, anti-STAT3, antiTyr580 phoshho-SHP2 (p-SHP2), anti-SHP2 (Cell Signaling Technology), anti-IL-6Ra and anti-gp130 (Santa Cruz). All secondary antibodies were from Dako.…”
Section: Western Blot Analysis and Qpcr Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…As a specific inhibitor of XIAP, embelin inhibits the action of XIAP inside cells through binding with the Smac binding site in the BIR3 domain in the XIAP protein molecule (9)(10)(11). Previous studies have demonstrated that embelin exhibits antitumor effects, and embelin at therapeutic dose can restrain the growth of various types of tumor cells including prostate cancer, pancreatic cancer, breast cancer and colon cancer (12)(13)(14)(15). According to another report, apoptosis of brain glioma cells is closely related to the mitochondrial pathway (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Embelin was shown to possess a broad spectrum of biological activities including antidiabetic (82), anti-inflammatory (83), and hepato-protective effects (84). In addition, embelin exhibits antitumor activity in many types of cancers such as breast (85), colon (86), prostate (87), and pancreatic cancer (88). Through computational structure-based computer screening, Wang et al (81) discovered that embelin is a potent inhibitor of X-linked inhibitor of apoptosis protein (XIAP), which partially explained its anticancer mechanism.…”
Section: Peg-derivatized Embelin As a Nanocarrier For The Delivery Ofmentioning
confidence: 99%